2020
DOI: 10.4274/mirt.galenos.2019.33866
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of <sup>18</sup>F-FDG PET/CT and KRAS Mutation in Colorectal Cancers

Abstract: Kolorektal kanserde KRAS mutasyonu ve tümörün lokalizasyonu ile ilişkili prognostik etki tartışmalı bir konudur. Bu nedenle 18 F-floro-2deoksi-glukoz pozitron emisyon tomografi/bilgisayarlı tomografi ( 18 F-FDG PET/BT) görüntülemede FDG tutulum paterni ile kolon kanseri tanısı almış hastalarda KRAS mutasyonu ve tümör lokalizasyonu arasındaki ilişkiyi değerlendirdik. Bu üç faktörün prognoz ve sağkalım üzerindeki etkileri değerlendirildi. Yöntem: Kolorektal kanser tanılı 83 hasta retrospektif olarak bu çalışmaya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The phantom was scanned on the same PET scanner where all patients were scanned with two bed positions for 15 min each to reduce image noise. Spherical VOIs with diameters matching those of the inner diameter of the phantom spheres (10,13,17,22,28, and 37 mm) were centered in the CT images of the phantom spheres and then copied to the same location in the registered PET images using the Hermes software. Then, the mean, peak and maximum SUV for each sphere were recorded to calculate the respective recovery coefficients as described below.…”
Section: Pet Image Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The phantom was scanned on the same PET scanner where all patients were scanned with two bed positions for 15 min each to reduce image noise. Spherical VOIs with diameters matching those of the inner diameter of the phantom spheres (10,13,17,22,28, and 37 mm) were centered in the CT images of the phantom spheres and then copied to the same location in the registered PET images using the Hermes software. Then, the mean, peak and maximum SUV for each sphere were recorded to calculate the respective recovery coefficients as described below.…”
Section: Pet Image Analysismentioning
confidence: 99%
“…However, others found that EGFR mutations correlate with NSCLC PET image features whereas KRAS mutations do not [22]. Similarly for CRC, one investigation of the effect of KRAS mutations on 2-[18F]FDG uptake of CRC lesions found no correlation [23], while others found statistically significant correlations for primary tumors [13,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS mutation has been associated with relatively higher rates of local failure or positive resection margins after thermal ablation or resection of CLM [11,12]. Recently, others have found that the coexistence of KRAS mutation with increased 2-[18F]FDG uptake is a negative prognostic factor in primary CRC [13]. KRAS mutation status has a predictive value also for image-guided ablation for lung adenocarcinoma [14].…”
mentioning
confidence: 99%
“…Therefore, KRAS mutant lesions may be distinguishable using images of metabolic activity. The manifestation of KRAS mutations in PET images has been studied for non-small cell lung cancer (NSCLC) patients [21,22] as well as for CRC [13,[23][24][25][26][27][28][29][30]. For NSCLC, one study showed that a multivariate model, including 2-[18F]FDG SUV MEAN , may be used as a predictive marker for KRAS mutations [21].…”
mentioning
confidence: 99%